Liability issues for environmental damage caused by military aggression of a terrorist country - I. V. Kyrieieva (Law and Safety)
The article focuses on the issues of liability for environmental damage caused by the military aggression of a terrorist country. The subject matter of the study is the impact of the consequences of military aggression against Ukraine on the state of its natural resources, the legal characterisation of these consequences in terms of liability and issues related to compensation for the damage caused. The purpose of the study is to outline the problems arising in the course of legal determination of the possibility of bringing a terrorist country which deliberately destroys natural resources to legal liability, and the difficulties arising in determining the extent of environmental damage caused. The research methods used, in particular, logical-semantic and dialectical, made it possible to consider the main features of the concept of “ecocide” as a crime against humanity and its direct connection with the genocide of the Ukrainian people.